Tenku Leadership Role in Planting the Character of Students in Manarul Border Dayah Islam, Aceh Tamiang District - Khoirul Bariyah; Zulheddi Zulheddi; Eka Susanti (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims: 1) To analyze the concept of cultivating the morals of the Islamic boarding school students of Manarul Islam Aceh Tamiang Border. 2) To analyze the implementation of instilling the morals of students in the Manarul Islam Aceh Tamiang Border Dayah. 3) To analyze the involvement of tengku in cultivating the morals of students in the Aceh Tamiang Manarul Islam Border Dayah. 4) To analyze the results of the leadership of the tengku in instilling the morals of the students at the Manarul Islam Aceh Tamiang Border Dayah. The method used in this research is a qualitative research method. The data collection techniques used in this study were interviews, observation, and documentation. The results of the study show that: 1) In realizing the concept of moral education in the Manarul Islam Border Dayah, it is applied using various methods. These methods include the uswah method (example), the ta'widiyah method (habitation), the mauiz'hah method (advice), the supervision method, the reward and punishment method, and the rote method. 2) The implementation of cultivating the morals of students at the Manarul Islam Border Dayah takes place inside and outside the classroom. 3) Tengku Mustafa's involvement in cultivating Santri Morals at the Manarul Islam Aceh Tamiang Border Dayah can also be seen from his leadership style, such as: democratic, charismatic, trustworthy, and effective leader. 4) The results of Tengku's Leadership in Instilling Santri Morals at the Manarul Islam Border Dayah Aceh Tamiang, there are several roles played by Tengku Mustafa Manarul Islam Border Dayah in empowering his role as an important person in shaping the morals of the santri even though in fostering the morals of the santri through several processes and use effective and efficient methods